The Steninae MacLeay, 1825 (Coleoptera: Staphylinidae) of Iran: identification key, checklist of species and a new synonymy - Serri, Sayeh; Frisch, Johannes (Zootaxa, 2016)
In this contribution to the knowledge of the Steninae MacLeay, 1825 of Iran we present an identification key to the 69 species known to occur in this country, which includes illustrations of the diagnostic genital characters of all species involved. The endophallic characters of the aedeagus of several Iranian species of Stenus Latreille, 1797 are illustrated for the first time. A critical checklist of the Steninae of Iran is presented at the province level. Stenus alanorum Ryvkin, 1990 is synonymized with S. medus Puthz, 1981.